PENGARUH KADAR Hb TERHADAP PRESTASI BELAJAR ANAK USIA SEKOLAH KELAS II-VI DI SDN SONOAGENG 6 PRAMBON NGANJUK - Dwi Yanti; Irwanto Irwanto; Arief Wibowo (The Indonesian Journal of Public Health, 2017)
Low hemoglobin (Hb) level said as anemia, would reduce the ability to learn and endurance. Students who suffer from anemia will not have a hight enthusiasm for learning because it is difficult to concentrate. Consequently, anemia indirectly affect the value of courses and learning achievement. The aim of research was to analysis hemoglobin (Hb) level which influents to study achievement school-age- children. Statistic test of the research was linier regression with α 0.05 by applying cross sectional approach. The sample taken by simple random sampling, and I got 67 respondents school – age – children class II–VI. The result of the research showed that Hb had significantly influent to study achievement school – age – children by analysed regresilinier on grade p = 0.002.Keywords: hemoglobin level, anemia, study achievement